Sulfate-Reducing Bacteria of the Oral Cavity and Their Relation with Periodontitis-Recent Advances - Kushkevych, Ivan; Coufalová, Martina; Vítězová, Monika; Rittmann, Simon K-M R (Journal of clinical medicine, 2020)
The number of cases of oral cavity inflammation in the population has been recently increasing, with periodontitis being the most common disease. It is caused by a change in the microbial composition of the biofilm in the periodontal pockets. In this context, an increased incidence of sulfate-reducing bacteria (SRB) in the oral cavity has been found, which are a part of the common microbiome of the mouth. This work is devoted to the description of the diversity of SRB isolated from the oral cavity. It also deals with the general description of periodontitis in terms of manifestations and origin. It describes the ability of SRB to participate in its development, although their effect on periodontal inflammation is not fully understood. The production of hydrogen sulfide as a cytochrome oxidase inhibitor may play a role in the etiology. A meta-analysis was conducted based on studies of the occurrence of SRB in humans.
Keywords: meta-analysis; SRB; sulfate-reducing bacteria; periodontal disease; oral cavity; periodontitis; dental plaque; sulfate; hydrogen sulfide